1991
DOI: 10.1111/j.1471-4159.1991.tb02032.x
|View full text |Cite
|
Sign up to set email alerts
|

12‐Lipoxygenase Products Attenuate the Glutamate Release and Ca2+ Accumulation Evoked by Depolarization of Hippocampal Mossy Fiber Nerve Endings

Abstract: Presynaptic correlates of evoked neurotransmitter release include a rise in cytosolic free calcium level and the calcium-dependent liberation of unesterified arachidonic acid. It has been proposed that lipoxygenase metabolites produced from arachidonic acid may constitute an endogenous feedback system for the modulation of neurotransmitter release. The results of the present study are in agreement with this hypothesis. It was demonstrated that membrane depolarization evoked the release of endogenous glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…It is of interest that the 12-lipoxygenase metabolites might act as a second messenger in Aplysia neurons (Piomelli et al 1987;Buttner et al 1989). Moreover, 12-lipoxygenase was shown to modulate glutamate release in hippocampal mossy fiber terminals (Freeman et al 1991;Dorman et al 1992). Our recent experiments demonstrated that the 12-lipoxygenase and/or its metabolites upregulated membrane excitability by targeting K ϩ channels in NG108-15 cells (Takahashi et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…It is of interest that the 12-lipoxygenase metabolites might act as a second messenger in Aplysia neurons (Piomelli et al 1987;Buttner et al 1989). Moreover, 12-lipoxygenase was shown to modulate glutamate release in hippocampal mossy fiber terminals (Freeman et al 1991;Dorman et al 1992). Our recent experiments demonstrated that the 12-lipoxygenase and/or its metabolites upregulated membrane excitability by targeting K ϩ channels in NG108-15 cells (Takahashi et al 1999).…”
Section: Discussionmentioning
confidence: 94%
“…45 Indeed, LOX metabolites were found to be synthesized in both neurons and glial cells. 21,[46][47][48] Some of them, such as 5-and 12-hydroxyeicosatetraenoic acids, have been reported to exert various actions on neurons, including modulation of Na-K ATPase activity, 49 neurotransmitter release 50 or alteration of membrane potential. 51,52 LOXs also act as regulators of cell proliferation and death, and have been implied in the mediation of apoptosis induced by various physical or chemical agents such as UV light, oxidative stress or receptor ligands 25,26 In contrast, only a small number of studies investigated the involvement of LOXs in the various signaling pathways leading to neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Several effects exerted by eicosanoids in the hippocampus are mediated by cyclooxygenase or lipoxygenase metabolites of AA (22,23). Indeed, AA was metabolized by hippocampal nerve terminals with the formation mainly of lypoxygenase products but also cyclooxygenase products (see dashed line in Fig.…”
Section: Exogenously Aa Facilitates the Evoked Outflow Of Adenomentioning
confidence: 99%